A postresection perfusion deficit in the right colon is an independent predictor of perioperative outcome after major hepatectomy. (23rd December 2021) - Birgin, Emrullah; Yang, Cui; Brunner, Anna; Hetjens, Svetlana; Rahbari, Mohammad; Bork, Ulrich; Reissfelder, Christoph; Weitz, Jürgen; Rahbari, Nuh N.
Abstract: Background: There is a strong interaction between hepatic hemodynamics and perfusion in the splanchnic system. However, little is known about differences in perfusion in different splanchnic compartments and their changes after hepatectomy. Methods: Perfusion in various splanchnic compartments (ie, stomach, small intestine, right and left colon, liver) was assessed pre‐ and post‐hepatectomy by intraoperative laser Doppler flowmetry. Differences of splanchnic perfusion between compartments were evaluated by ANOVA, and risk factors of postoperative complications (graded by the comprehensive complication index [CCI]) were analyzed by univariate and multivariate analyses. A prediction model of postoperative complications was developed. Results: A total of 50 and 29 patients with major and minor hepatectomy were enrolled. Splanchnic perfusion at baseline varied significantly across different splanchnic compartments with highest values in the small bowel and right colon ( P < .001). Major hepatectomy induced a significant perfusion decrease in the stomach ( P = .006), right colon ( P < .001) and small bowel ( P = .035). A postresection perfusion deficit in the right colon with values below 254 perfusion units (PU) was identified as an independent predictor of clinically relevant complications after major hepatectomy (concordance index: 0.79, 95% CI 0.66‐0.87, P = .002). Bootstrap validation confirmed internal validity and excellent calibration. Conclusions: Major hepatectomy causes significant reduction of splanchnic perfusion. An intraoperative posthepatectomy microcirculatory perfusion deficit of the right colon is a strong and independent predictor of clinically relevant postoperative complications after major hepatectomy. Abstract : The impact of hepatectomy on splanchnic perfusion has been poorly documented. In this study Birgin and colleagues revealed that major hepatectomy induces a significant reduction in splanchnic perfusion. A postresection microcirculatory perfusion deficit in the right colon was identified as a strong and independent predictor of a complicated postoperative course.